Pulmonary Diseases and Periodontal Health- A Review - Bhardwaj, Dr. Vinay Kumar; Fotedar, Dr. Shailee; Negi, .Dr. Nishant; Chauhan, Dr. Atul (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The oral cavity has a multitude of functions in relation to daily life. The poor health has the potential of affecting the quality of life. In recent years, efforts have been made to recognize oral health as an integral part of overall health. The anatomical continuity between the lungs and the oral cavity makes the latter a potential reservoir of respiratory pathogens. The microorganisms may enter the lung by inhalation, but the most common route of infection is aspiration of what pneumologists have long referred to as oropharyngeal secretions. There is a fair evidence exists between respiratory disorders and poor oral hygiene & good evidence exist that improved oral health and professional oral health care reduce the progression or occurrence of respiratory diseases among high risk adults. Dental plaque can act as a reservoir for respiratory infections. Microorganisms can be released from the dental plaque into salivary secretions, which are then aspirated into lower respiratory tract to cause respiratory diseases like pneumonia and chronic obstructive pulmonary disease. Periodontal diseases and respiratory diseases including bronchial asthma have an inflammatory nature thus mandates a positive correlation between these. This paper discusses the relation between the periodontitis, its influence on the incidence of respiratory disorders and underlines the importance of improving oral hygiene among patients who are at risk.